Review of the wolf-spider genus Draposa Kronestedt, 2010 from China (Araneae, Lycosidae) - Zhi-Sheng Zhang; Piao Liu; Shuqiang Li; Lu-Yu Wang (ZooKeys)
The wolf-spider genus Draposa Kronestedt, 2010 in China is reviewed. A new combination is proposed: Draposa aciculifera (Chen, Song & Li, 2001), comb. nov. (ex. Pardosa C L. Koch, 1847). Pardosa shugangensis Yin, Bao & Peng, 1997 is synonymized with Draposa zhanjiangensis (Yin, Wang, Peng & Xie, 1995), syn. nov. Detailed redescriptions, habitus photographs, illustrations of copulatory organs, and live habitus images are provided for relevant species. Draposa burasantiensis (Tikader & Malhotra, 1976) is transferred back to Pardosa and figures of P. burasantiensis sensu Yin et al. (1997b) from China are provided.